Validity of Yin-Yang temperament in Sasang Personality Questionnaire - Bo Kyung Hwang; Yeo-Jin Yoon; Sang Yun Han; Soo Jin Lee; Han Chae (Integrative Medicine Research)
Background: The Yin-Yang is a pivotal concept of traditional East-Asian medicine, however the stability of Yin-Yang temperament in Sasang Personality Questionnaire (SPQ) over time has not been extensively studied. The purpose of this study was to examine the test-retest validity of SPQ with a large number of participants. Methods: SPQ test was conducted two times with three months interval in 247 Korean university students. The structural validity of first SPQ data was examined with Factor analysis and Cronbach's alpha, and the correlation between first and second measure of SPQ was attested with Pearson's correlation. Yang, Uncertain and Yin temperament groups were determined with SPQ total scores, and agreement of temperament group clustering between first and second measures were analyzed with Cohen's Kappa. Results: Three subscales of SPQ explained 55.25% of total variances, and internal consistency of SPQ total score was 0.772. The correlation coefficient between first and second measures of SPQ were 0.851 and 0.888 in male and female, respectively, and the agreement of first and second Yin-Yang temperament group clustering as Cohen's Kappa was 0.536 for male and 0.637 for female. Conclusion: The repeatability of SPQ measuring Yin-Yang temperament at three months of interval was found to be satisfactory. The SPQ would be a reliable clinical measure for the biopsychological studies of traditional East-Asian medicine. Keywords: Body Mass Index, Sasang Personality Questionnaire, Repeatability, University students, Yin-Yang temperament